Genetic syndromes and developmental risk for autism spectrum and attention deficit hyperactivity disorders: insights from fragile X syndrome - Doherty, B; Scerif, G (Wiley, 2017)
Many genetic markers are associated with atypical developmental outcomes. In this article, we review evidence from studies on the most common inherited cause of intellectual disability, fragile X syndrome (FXS). We aim to highlight general developmental consequences as well as specific implications for autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), including the complexity of characterizing ASD and ADHD symptoms in FXS. We address three issues: First, links among genes, brain, and cognition need to be situated in a developmental context, even in a monogenic disorder like FXS. Second, the comparatively early age of diagnosis of FXS offers the opportunity to study developmental trajectories of risk and resilience for a complex, behaviorally defined disorder highly associated with FXS but diagnosed later: ASD. Third, the high occurrence of both ASD and ADHD in FXS allows for a novel investigation of their comorbidity, with important caveats.